THE CONTINUATION OF THE COCONUT PRODUCT COOPERATIVE IN NORTH MALUKU PROVINCE, INDONESIA - 1Munawir Muhammad, 2Djoko Koestioni, 3Syafrial, 4Riyanti Isaskar, (Chelonian Research Foundation, 2024)
The coconut plant, long known to the people of Indonesia, is widespread throughout the archipelago. As a strategic commodity, coconut plays a crucial role in the social, cultural, and economic aspects of Indonesian society. Coconut production in Indonesia reaches 18.3 million tons, making it the highest in the world. This research aims to analyze the condition of sustainable livelihood assets within coconut processed product cooperatives using the pentagon model. Data collection involves average asset values based on categories such as Human Capital, Natural Capital, Financial Capital, Social Capital, Physical Capital, Entrepreneurship Capital, and Political Capital. The analysis results show variations in the average asset values, with Physical Capital and Entrepreneurship Capital having the highest values, while Political Capital has the lowest. This indicates that coconut processed product cooperatives excel in physical, financial, and entrepreneurial aspects, while also strengthening political support and social capital. Keywords: Sustainable Livelihood, Coconut Commodity